Pengaruh Kepuasan Kerja, Lingkungan Kerja Dan Budaya Kerja Terhadap Komitmen Kerja Karyawan Pada PT. Sumber Sawit Makmur Kabupaten Batu Bara - Diyan Dwi Lestari; Normansyah Normansyah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to determine the effect of job satisfaction, work environment and work culture partially on employee work commitment at PT. Sumber Sawit Makmur, Batu Bara Regency. This type of research is quantitative descriptive, data analysis uses multiple linear regression and involves a sample of 54 respondents determined by the slovin method from a total of 117 employees. The results of the study through the regression equation are Y = 3.190 + 0.190X1 + 0.257X2 + 0.249X3. The results of the t-test prove that H1 is accepted, namely partially job satisfaction influences work commitment with a t-count value (2.942) > t-table (2.007), partially the work environment influences work commitment with a t-count value (3.046) > t-table (2.007) and partially work culture influences work commitment with a t-count value (2.134) > t-table (2.007). The F-test results confirmed that H2 was accepted, namely that job satisfaction, work environment, and work culture simultaneously influence work commitment, with the calculated F value > F table (22.726 > 2.79).